AB1318 Practical aspects of biological-drug monitoring in rheumatoid arthritis and spondyloarthritis. (12th June 2018) - Rosas-Gómez de Salazar, J.; Martín-López, M.; Oton, T.; Carmona, L.; Balsa, A.; Calvo-Alén, J.; Sanmarti, R.; Tornero, J.
Abstract : Objectives: To prepare recommendations on practical aspects of biological-drug monitoring that may be useful for rheumatologist Methods: A systematic review of the literature was carried out to determine in which patients and in what clinical circumstances may be most beneficial to monitor the levels of biological drugs and their antibodies in patients suffering Rheumatoid Arthritis (RA) and/or Spondyloarthritis (SpA). With the results of the review, a group of experts produced a series of clinical questions, to be answered through the available scientific evidence, and then, subsequently, to make the recommendations and clinical algorithms for instructing the decision-making process. Results: Results from the systematic review showed that the biological-drug monitoring might be especially useful in two clinical situations; in case of a treatment failure (primary or secondary) and in sustained remission (see figure 1). It was also reviewed which laboratory technique might be better and the optimal time for blood withdrawal. Specific recommendations are given on the interpretation of drug levels and on factors that should be taken into account are given (i.e. body mass index and concomitant medication). Conclusions: Informed algorithms have been developed regarding the optimal time for requesting drug levels and anti- drug antibodies in patients with RA and SpA. This recommendations may help in the decision-making process and could be useful as part of future guidelines in the field. Acknowledgements: This study was funded by Grifols through the Asociación para la Investigación en Reumatología de la Marina Baixa (AIRE-MB). The content is solely the responsibility of the authors and does not necessarily represent the official views of Grifols. Disclosure of Interest: None declared